A GENERAL REVIEW OF ZIMBABWE’S RESPONSE TO DRUG AND SUBSTANCE ABUSE AMONG THE YOUTH - Maraire, Tariro; Chethiyar, Saralah Devi Mariamdaran; Jasni, Mohd Alif Bin (PEOPLE: International Journal of Social Sciences, 2020)
Drug abuse among the youth in Zimbabwe has reached crisis levels, and the number of youths engaging in drug abuse is increasing yearly. The purpose of this study was analysing the response, and efforts made by the Government of Zimbabwe, and its stakeholders, civic organizations, and the Zimbabwean community to addressing the problem of drug abuse by the youth in the country. The study used a qualitative research method, in the form of desk research by analyzing secondary data in the form of books, peer-reviewed articles, and relevant websites. Findings from the study showed that the Zimbabwean Government, and its stakeholders, civic organizations, and the community have in place strategies for drug abuse rehabilitation, and prevention in Zimbabwe; however, the problem of drug abuse is recurring and increasing among the youth population. The study also found out that, though the church plays a significant role in addressing social issues, and a voice, listened to in the community; there is no Psycho- Christian based rehabilitation module for youth drug abusers in Zimbabwe. The study concluded that there is a need to widen intervention programs for youth drug abusers in Zimbabwe. The study recommends for future studies to look into the idea of establishing a Christian based rehabilitation module for youth drug abusers in Zimbabwe, to support the youth drug abusers in recovery and quitting.